Disturbed eating behaviours do not impact treatment response in a paediatric obesity chronic care treatment programme. (6th November 2019) - Fogh, Mette; Lund, Morten A V; Mollerup, Pernille M; Johansen, Mia Ø; Melskens, Rikke H; Trier, Cæcilie; Kloppenborg, Julie T; Hansen, Torben; Holm, Jens‐Christian
Abstract : Aim: This study investigates the prevalence of disturbed eating behaviours in children and adolescents initiating obesity treatment, and how the prevalence varies with age, sex and body mass index (BMI) standard deviation score (SDS). Secondly, it examines whether the presence of disturbed eating behaviours at enrolment is associated with the degree of weight loss after 12 months of treatment. Methods: A total of 3621 patients aged 3–18 years enrolled in a multidisciplinary obesity treatment programme were studied. Follow‐up data after a median of 12.4 months were available for 2055 patients. Upon entry, patients were assessed for the following disturbed eating behaviours: meal skipping, emotional eating, overeating and rapid eating. Height and weight were measured at baseline and follow‐up. Results: At enrolment, median age was 11.4 years, median BMI SDS was 2.87, and 82.2% of patients exhibited one or more disturbed eating behaviours. The prevalence of meal skipping, emotional eating and rapid eating increased with age ( P < 0.01). Patients who reported overeating or rapid eating exhibited a 0.06–0.11 higher BMI SDS at enrolment than patients without these disturbed eating behaviours ( P < 0.02). After 1 year of treatment, BMI SDS was reduced in 75.7% of patients, and the median reduction was 0.24 (95% confidence interval: 0.22–0.27). Overeating was associated with a higher degree of weight loss, while meal skipping, emotional eating and rapid eating did not associate with the degree of weight loss at follow‐up. Conclusions: Disturbed eating behaviours were highly prevalent in children and adolescents with overweight or obesity, and varied with age and sex. After 1 year of treatment, the degree of obesity improved, regardless of the presence of disturbed eating behaviours at treatment initiation.